2022
DOI: 10.3390/ijms231911531
|View full text |Cite
|
Sign up to set email alerts
|

AtGSTU19 and AtGSTU24 as Moderators of the Response of Arabidopsis thaliana to Turnip mosaic virus

Abstract: Plants produce glutathione as a response to the intercellular redox state. Glutathione actively participates in the reactive oxygen species (ROS)-dependent signaling pathway, especially under biotic stress conditions. Most of the glutathione S-transferases (GSTs) are induced in cells during the defense response of plants not only through highly specific glutathione-binding abilities but also by participating in the signaling function. The tau class of GSTs has been reported to be induced as a response under st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(40 citation statements)
references
References 108 publications
3
37
0
Order By: Relevance
“…The changes in the expression of TuMV-CP during TuMV infection in rbohD , rbohF , and rbohD/F mutant plants confirmed the differences in the reaction of these plants to the presence of TuMV. Moreover, our previous works confirmed that RbohD [ 24 ] and glutathione [ 39 , 40 ] act as modulators of reaction to different Potyviruses. In normal physiological conditions, the levels of Rboh s and glutathione are precisely regulated in plants.…”
Section: Resultsmentioning
confidence: 52%
See 4 more Smart Citations
“…The changes in the expression of TuMV-CP during TuMV infection in rbohD , rbohF , and rbohD/F mutant plants confirmed the differences in the reaction of these plants to the presence of TuMV. Moreover, our previous works confirmed that RbohD [ 24 ] and glutathione [ 39 , 40 ] act as modulators of reaction to different Potyviruses. In normal physiological conditions, the levels of Rboh s and glutathione are precisely regulated in plants.…”
Section: Resultsmentioning
confidence: 52%
“…Moreover, the relative expression of AtGGT1 decreased systemically after 3 dpi by 4.45-fold in virus-inoculated Col-0 and by 21-fold in virus-inoculated rbohD plants. Our previous investigation showed that GSTs (glutathione S-transferases), especially class tau (GSTU), play an important role in the modulation of cell glutathione levels in TuMV infection [ 40 ]. Moreover, modification of the expression of different GST genes was found to be crucial for the precise modulation of the host’s response to this viral pathogen [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations